The exodus of German psychologist and its consequences - Lück, Helmut E. (2000)
The author analyzes the consequences of the emigration of German psychologists in the years of the rise of Nationalsocialism and its influence both for German psychology and emigrants. Particularly, the destiny of David Katz, Kurt Lewin and Wolfgang Köhler in the emigration is reviewed, pointing out how the process of exile influenced their scientific work. The author analyzes also the reaction of William Stern after his dismissal as Profesor of the University of Hamburg. Finally, the author refers to postwar years and how German psychology was reconstituted.